Drug interactions between cephalosporins and 5-FU-based chemotherapy in the treatment of patients with gastrointestinal cancer - an exploratory cohort analysis - Siegel, Robert; Schlosser-Hupf, Sophie; Müller-Schilling, Martina; Kharroubi, Samer A.; Gessner, André; El-Najjar, Nahed (Frontiers in Pharmacology, 2025)
IntroductionChemotherapeutic agents, despite their toxicities, variability in individual response, and risk of drug-drug interactions, are essential in the treatment of gastrointestinal cancers. Due to their immunosuppressed state, cancer patients often require concurrent antibiotic therapy, most commonly with cephalosporin antibiotics (CAB) (β-lactams), for treatment or prophylaxis of infections. However, little is known about potential interactions between CAB and antineoplastic agents, such as 5-Fluorouracil (5-FU), Capecitabine, and Trifluridine/Tipiracil.MethodsThis retrospective study aimed to evaluate the impact of CAB therapy on the efficacy and toxicity of these chemotherapeutics in patients treated at the University Hospital Regensburg, Germany. A total of 19 cancer patients receiving CAB were compared with 19 optimally matched controls who did not receive CAB. Matching criteria included age, sex, cancer type, chemotherapy regimen, and cycle interval.ResultsCAB-treated patients experienced a median delay of 6 days in receiving the subsequent chemotherapy cycle, likely reflecting infection-related vulnerability. Despite this, the CAB group demonstrated improved clinical outcomes, with a reduction in tumor progression, an increase in stable disease and tumor regression staging results compared to the control group (p = 0.049). The CAB group also showed a more favorable side effect profile, with milder toxicity despite higher overall medication burden. Notably, when CAB were used alone and for longer durations, side effects remained low.Discussion and ConclusionCollectively, concomitant use of cephalosporins with 5-FU, Capecitabine, or Trifluridine/Tipiracil does not impair antitumor efficacy or increase toxicity. Of clinical relevance, CAB therapy enhances clinical outcomes and survival, highlighting the need for further prospective studies on specific antibiotic-chemotherapy interactions.